THE PHILOSOPHICAL IDEAS OF RAJA MAHENDRA PRATAP SINGH - Tarun Prakash; Hridayesh Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
This study examines the multilayered philosophical perspective of Raja Mahendra Pratap Singh—a visionary freedom fighter, educator, and worldwide intellectual—emphasizing the lasting significance of his ideas in the 21st century. Pratap’s philosophy, grounded in a distinctive amalgamation of Indian spiritual traditions and contemporary socio-political values, advocates for universalism, anti-casteism, religious pluralism, ethical socialism, and global humanism. Through his notion of the "Religion of Love," he envisioned a spiritually cohesive world that transcends sectarian boundaries. His promotion of social transformation, especially via inclusive and ethical education, contested the hierarchical frameworks of both colonial and traditional Indian society. He established India's inaugural polytechnic to advance technical education integrated with ethical principles. Rejecting caste markers, encouraging interfaith cooperation, and upholding spiritual egalitarianism were all aspects of Pratap’s secularism. His advocacy for a World Federation and his condemnation of ethically weak political ideologies established him as a forerunner to contemporary concepts of global citizenship. This study contends that Raja Mahendra Pratap’s life and philosophy provide a significant framework for tackling modern issues such as communal a divide, educational disparity, caste prejudice, and geopolitical strife.